Access to post‐acute care services reduces emergency department utilisation among individuals insured by Medicaid: An observational study. Issue 5 (8th July 2021) - Brom, Heather; Anusiewicz, Colleen V.; Udoeyo, Idorenyin; Chittams, Jesse; Brooks Carthon, J. Margo
Abstract: Aims and objectives: We examined whether access to post‐acute care services differed between individuals insured by Medicaid and commercial insurers and whether those differences explained emergency department utilisation 30 days post‐hospitalisation. Background: Timely follow‐up to community‐based providers is a strategy to improve post‐hospitalisation outcomes. However, little is known regarding the influence of post‐acute care services on the likelihood of emergency department use post‐hospitalisation for individuals insured by Medicaid. Design: We conducted a retrospective observational study of electronic health record data from an academic medical centre in a large northeastern urban setting. The STROBE checklist was used in reporting this observational study. Methods: Our analysis included adults insured by Medicaid or commercial insurers who were discharged from medical services between 1 August–31 October 2017 ( n  = 785). Logistic regression models were used to examine the effects of post‐acute care services (primary care, home health, specialty care) on the odds of an emergency department visit. Results: Post‐hospitalisation, 12% ( n  = 59) of individuals insured by Medicaid experienced an emergency department visit compared to 4.2% ( n  = 13) of individuals commercially insured. Having Medicaid insurance was associated with higher odds of emergency department visits post‐hospitalisation (OR = 3.24). Having a home care visit or specialty care visit within 30 days post‐discharge were significant predictors of lower odds of emergency department visits. Specific to specialty care visits, Medicaid was no longer a significant predictor of emergency department visits with specialty care being more influential (OR = 0.01). Conclusions: Improving connections to appropriate post‐acute care services, specifically specialty care, may improve outcomes among individuals insured by Medicaid. Relevance to clinical practice: Hospital‐based nurses, including those in direct care, case management and discharge planning, play an important role in facilitating referrals and scheduling appointments prior to discharge. Individuals insured by Medicaid may require additional support in accessing these services and nurses are well‐positioned to facilitate care continuity.